Fargo. The complete first season [videorecording (DVD)] - Thornton, Billy Bob; Hanks, Colin, 1977-; Freeman, Martin, 1971-; Coen, Joel; Coen, Ethan (MGM Television Entertainment, 2014)
The Coen Brothers' Best Picture Oscar Nominee transforms into television drama. It features a new "true crime" story and new characters, all chilled in the trademark dry wit, murderous mayhem and "Minnesota nice" of the original classic film. Lorne Malvo is a manipulative master criminal who changes the life of insurance salesmen Lester Nygaard. Gus Grimly and Molly Solverson are the small-town police officers who join forces to uncover Lester's secrets.